A PRAGMATIC INVESTIGATION OF BLESSINGS AND WISHES IN ENGLISH AND UZBEK (Ustozlar uchun, 2025)
Blessings and wishes serve as key speech acts conveying goodwill and hope in interpersonal communication. This study investigates their pragmatic functions and grammatical realizations in English and Uzbek, analyzing modality markers, sentence structures, and lexical choices. Data were drawn from spoken and written corpora, religious texts, and folk literature. The contrastive analysis shows that English employs modal auxiliaries and subjunctive moods, while Uzbek uses morphological suffixes and particles for modality. Cultural and religious backgrounds influence the linguistic expression in both languages. The study highlights implications for translation, language teaching, and cross-cultural understanding.